Non-destructive quality monitoring of stored tomatoes using VIS-NIR spectroscopy - Saad A.; Jha S.N.; Jaiswal P.; Srivastava N.; Helyes L. (My University, 2025)
The postharvest quality and storage life of vegetables are controlled by maturity due to their cells still alive after harvest and continue their physiological activity. The objective of this study was to monitoring physico-chemical quality parameters of intact tomato (Lycopersicum esculentum) during storage (18 °C, 85% RH) for 12 days, based upon visible/near-infrared (VIS/NIR) absorbance spectroscopy from 350 nm to 1050 nm. Partial least squares regression (PLSR) was applied to estimate soluble solids content (SSC), Titratable acidity (TA), and lycopene content of the tomatoes. The PLSR calibration model with SSC at 12 days storage, gave the highest coefficient of determination (R2) = 0.91, root mean squared error of prediction (RMSEP) = 0.285 and bias = -0.003. While the lowest R2 with lycopene (0.73) and bias of -0.002 at harvesting day. Changes of sweetness index (SI), SSC, TA and lycopene content varied from 7.16 to 11.39, 4.25 to 5.51 °Brix, 0.5936 to 0.4837% and 8.65-42.69 mg/kg fresh tomato, respectively. While, Hunter colour values L∗, a∗, and b∗were changed from 60.5 to 38.86, -2.85 to 36.59 and 37.07 to 30.92, respectively. The results showed that physico-chemical quality parameters changes significantly during storage of turning maturity tomatoes and have potential application in the field of post-harvesting. © 2015 Asian Agricultural and Biological Engineering Association Published by Elsevier B.V. All rights reserved.